CBT formulation in practice : a survey amongst Icelandic Psychologists - María Guðmundsdóttir 1986- (2019)
Case formulation (CF) is considered a core skill of Cognitive Behaviour Therapy (CBT) but there is lack of research on how it is applied in practice. The objective of this study was to investigate how clinical psychologists in Iceland report use of CF in CBT in practice. The study aimed to evaluate if the psychologists understanding of the structure of CF and how it should be applied in practice differed according to place of obtaining clinical degree in psychology, education level, clinical experience and training in CBT and CBT CF. Assessment was made by an online self-report questionnaire (PTFQ-IS) which was originally made by Zivor, Salkovskis & Oldfield (2013) but translated and adapted to suit the purpose of this study. The survey was sent to all registered clinical psychologists within the Icelandic Psychological Association (IPA). A total of 107 participants completed the survey. Participant’s ratings of their level of expertise in CBT was on average measured high and competence in CBT CF rated moderate. Participants estimated all 13 psychological processes in making an initial CBT CF of high importance. Sharing and modifying the initial and modified CBT CF with clients was reported mostly done very frequently and the initial CBT CF most often shared in the 2nd session. More hours of monthly supervision were reported by participants receiving it from employers than those who were self-employed. The time in supervision spent discussing CBT CF was on average 20-39%. This study indicated that clinical experience was the strongest of the independent variables in predicting variance in participant’s responses. The sample was not large enough for the results to be definitive and the homogeneity of the sample caused difficulties in comparing groups within the sample. Keywords: Case-formulation, CBT, survey, case-formulation, assessment, clinical training